2014
DOI: 10.1007/s13524-014-0283-z
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Neighborhoods Using Common Destinations: Social Characteristics of Activity Spaces and Home Census Tracts Compared

Abstract: Research on neighborhood effects has focused largely on residential neighborhoods, but people are exposed to many other places in the course of their daily lives—at school, at work, when shopping, and so on. Thus, studies of residential neighborhoods consider only a subset of the social-spatial environment affecting individuals. In this article, we examine the characteristics of adults’ “activity spaces”—spaces defined by locations that individuals visit regularly, in Los Angeles County, California. Using geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 57 publications
7
152
2
2
Order By: Relevance
“…Seven of the nine participants in the smallest activity space size category (<5 km) have lives in these spaces that converge with traditional understandings of community: a physical presence in a geographic area that includes social contact with others and engagement with meaningful places. These participants were strongly connected to cultural or religious communities or social service organizations, which were located in close proximity to their home addresses (ID 15,8,4,2,16,27,28). For these participants, small activity spaces reflected social ties within a local geographic area, consistent with results from previous studies where people with smaller activity spaces were shown to experience a stronger sense of community.…”
Section: Patterns In Activity Spaces: Understanding Presence In the Csupporting
confidence: 82%
See 1 more Smart Citation
“…Seven of the nine participants in the smallest activity space size category (<5 km) have lives in these spaces that converge with traditional understandings of community: a physical presence in a geographic area that includes social contact with others and engagement with meaningful places. These participants were strongly connected to cultural or religious communities or social service organizations, which were located in close proximity to their home addresses (ID 15,8,4,2,16,27,28). For these participants, small activity spaces reflected social ties within a local geographic area, consistent with results from previous studies where people with smaller activity spaces were shown to experience a stronger sense of community.…”
Section: Patterns In Activity Spaces: Understanding Presence In the Csupporting
confidence: 82%
“…Typically in studies examining the derivation of activity space areas, the Standard Deviational Ellipse (SDE) has been used to determine the directional distribution of a person's use of spaces. [16][17][18][19] While this approach provides a strong indication of the direction of a person's activities within their proximal community, outlier activity points can lead to an overestimation of the size of activity space. [20][21][22][23][24] To address this problem, the current study used a mean circle approach.…”
Section: Participatory Social Mappingmentioning
confidence: 99%
“…Less educated individuals tend to consume more takeaway foods than do more highly educated individuals (Miura, Giskes, & Turrell, 2012), and there is some evidence that the consumption of takeaway foods high in sugar and salt can explain differences in body mass index between the least and most educated (Miura & Turrell, 2014). As such, the effects of the local food environment on weight status may be strongest in people of low SES because their activity spaces-that is, the areas they use for their daily routines-are generally smaller than those of individuals of high SES (Jones & Pebley, 2014), leading to a higher dependence on the direct neighborhood environment.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple methods have been proposed for converting raw spatial information into a representation of an activity space [21], such as the use of Census Tracts [22,36], the characteristics of known destinations [23], or constructing standard deviational ellipses from location information [37,38]. Tailored approaches include travel time polygons describing an area of potential travel, road network buffers of routes to regular destinations, or daily path areas constructed from actual routes taken [17,39].…”
Section: Activity Space Analysismentioning
confidence: 99%
“…This is important since recent research has shown that environmental characteristics of such non-residential places are associated with health-related outcomes, such as self-rated health [16] and dietary intake [17][18][19]. Therefore, a growing number of studies on health, place, and mobility are using an analytical approach that involves constructing an activity space for each participant (e.g., [20][21][22][23]). This concept, proposed by space-time geographers, describes the portion of the environment actually used by an individual to fulfill activities and travel between locations [24][25][26].…”
Section: Introductionmentioning
confidence: 99%